Corrosion behaviors of basalt fiber exposed to the acids. (17th January 2022) - Li, Meng; Xing, Dan; Zheng, Qing-Bin; Li, Hui; Hao, Bin; Ma, Peng-Cheng
Highlights: Corrosion behaviors of basalt fiber (BF) exposed to various acids were studied. H + concentration in acid was the most influential factor for the corrosion of BF. SO4 2− in H2 SO4 acted as an accelerator for the corrosion of BF. Axial and spiral cracks were formed on fiber surface with presence of acid. The axial defects on BF surface were caused during the spinning of fiber. Abstract: In this work, Taguchi method was employed to elaborate the effects of temperature, concentration and immersion time of typical acids (HCl, H2 SO4, HNO3 ) on the morphology and tensile strength of basalt fiber (BF). The results showed that the corrosion behavior of BF was controlled by the ion-exchange process with presence of H + ions, and irregular and spiral cracks were formed during this process, which led to the severe degradation on the tensile strength of fiber. Besides the governing role of H + concentration in acids, SO4 2- also aggravated the corrosion in sulfuric acid with precipitant of CaSO4 . The reasons behind the acid-induced low-energy crack opening paths were given to illustrate the formation of spiral cracks on fiber surface in acids. The ubiquitous axial defects were revealed on fiber surface, and comparative results confirmed that such defects originated from the scratching between the filament and bushing during the fiber spinning process.